pH Restraints on Lettuce Fruit Germination - REYNOLDS, T. (Oxford University Press, 1975)
The effects of buffers with a range of pH values and of concentrations low enough to exert negligible osmotic stress on germination of lettuce ( Lactuca saliva L. cv. Arctic King) fruits were examined. No restraints were noted except at extremes of pH. Furthermore inhibition in hydrochloric acid or potassium hydroxide solutions was not evident below concentrations of about 0.05 M. Acetic acid or ammonium hydroxide were very much more inhibitory but their salt, ammonium acetate, only inhibited when its concentration reached a sufficiently high level to operate by osmotic stress. Inhibition by a series of organic acids and bases showed a positive correlation with the lipophilie nature of the molecule although there were some unexplained exceptions. In contrast with previous cases of germination inhibition the effect was not produced by a lowering of the upper temperature cut-off point but by an overall lowering of total germination at all temperatures. This is taken to indicate a toxic effect of pH extremes rather than a true inhibition.